The Obstetric Panorama in the Metropolitan Region of Baixada Santista – Brazil: Prevalence and Profile of Parturients: Prevalence and Profile of Parturients (Epidemiology, Biostatistics, and Public Health, 2025)
Background: The birth of a child is a significant milestone for mothers and families. However, concerns regarding the type and safety of delivery persist. Evidence shows that vaginal delivery provides immunological and respiratory benefits for the baby and offers protective factors for the mother. Despite this, cesarean sections remain prevalent, particularly in developing regions.Objective: This study aimed to analyze delivery data from the Região Metropolitana da Baixada Santista (RMBS) between 2019 and 2022, identifying the predominant delivery method and examining the socioeconomic and cultural profiles of mothers.Methods: Data was obtained from the TABNET/DATASUS database in the Live Birth Information System (SISNAC).Results: Between 2019 and 2022, 86,198 deliveries were recorded, with 53% being cesarean sections and 47% vaginal deliveries, exceeding the 15% cesarean rate recommended by the WHO. Vaginal delivery was more common among mothers aged 10–24 years, while cesarean sections predominated among those aged 25–54 years. Women with 1–11 years of education favored vaginal delivery, while those with ≥12 years of education had cesarean rates more than double vaginal deliveries. Cesarean sections were more prevalent among white and yellow ethnicities. Single mothers predominantly chose vaginal delivery, whereas married, widowed, separated, or cohabiting women favored cesarean sections.Conclusion: The high prevalence of cesarean deliveries in RMBS appears to be associated with maternal age, education level, socioeconomic status, marital status, and prenatal care access. These findings highlight the need for targeted interventions to promote evidence-based delivery practices.
Keywords: cesarean delivery; vaginal delivery; normal delivery; live birth; prenatal; epidemiology